Religious revivals in the light of modern psychological theory - Grimshaw, Ivan G. (The University of Edinburgh, 1933)
A. A BRIEF CONSIDERATION OF THE RISE AND DEVELOPMENT OF THE SCIENCE OF THE PSYCHOLOGY OF RELIGION. Approximately a half century ago Religion "which had seen every other department of human life and activity succumb to the conqueror, Psychology, was in turn subjected to the scalpel and scrutiny of science". From 1882 when Dr. G. Stanley Hall of Clark University published his pioneer article, until the present time, the interest in this subject of the psychology of religion, and the output of books upon it, have continued to increase. (1) THE CONTRIBUTION OF THE AMERICAN SCHOOL. (a) EARLY WRITINGS. Credit for the early impetus must be given to Dr. Hall and the men he drew around him at Clark, We owe much to Burnham,. Daniels, and Lancaster, even though their contribution was chiefly to pedagogical theory, and still more to Starbuck, and Leuba. Starbuck published the first really elaborate scientific study of religious phenomena, a book which "marked an epoch in the history of American religious psychology." Contemporary with the valuable contributions of the Clark University group was the work done by Gulick, and Coe. It remained, however, for the inimitable William James to popularize the subject by his now classic Gifford Lectures delivered at Edinburgh at the beginning of this century. (b) MORE RECENT DEVELOPMENTS. From 1903 onward the literature has grown by leaps and bounds so that we have excellent American studies made by Moses in 1906, Pratt in 1907, and in 1924, Reudiger also in 1907, Tawney and Cutten in 1908, Marshall in 1909, King and Anies in 1910, Leuba in 1912, Kate in 1915, Coe and Snowden in 1916, Stratton in 1918, Wright and Strickland in 1924, Hickman and Josey in 1926, Mahoney and Jordan in 1927, and Dresser and Clark in 1929. (2) THE CONTRIBUTION OF BRITISH THINKERS. British scholars also have contributed to this great movement as evidenced by the work of Galloway in 1909, Stevens in the Ounningham Lectures of 1911, Stalker in the James Sprunt Lectures of 1914, Swisher, Howley, Guttery and Annett in 1920, Pym in 1921, Thouless in 1923, Selbie in 1924, Paterson in his famous Gifford Lectures delivered at Glasgow in 1924-5, Underwood and Mathews in 1925, Edward in the Kerr Lectures published in 1926, Flower in 1927, Valentine and Pitts in 1929, and Lang in 1931. (3) THE CONTRIBUTION OF CONTINENTAL SCHOLARS. Although the science of the psychology of religion was born and seems to have flourished best in America, and while excellent work has been done in the field by British scholars, the investigations of certain continental authorities must not be ignored. The French represented by Delacroix, Plournoy, Allier, and Revault-D'Allones; the Germans by such men as Oesterreich and Wobbermin; the Danes by Schou and the Italians by De Sanctis have added much to our knowledge of the subject. It is interesting to note concerning the listed books, that of those published since 1900, thirty deal with the psychology of religion in general, four with mysticism, two with the more pathological aspects of religious life, and ten with conversion. Thus there was published in a little more than thirty years, a total of forty-six books to say nothing of hundreds of articles. B. A STUDY OF THE WORK DONE ON THE PSYCHOLOGY OF RELIGIOUS REVIVALS. In the foregoing discussion any books dealing with the phenomenon of the religious revival have been deliberately ignored. However, as an outgrowth of this interest in the psychology of religion we would expect attention to be centered upon the ever-recurring phenomenon of religious revival. (1) THE WORK ALREADY DONE. Almost one hundred and fifty years before psychology was considered a distinct science certain notable contributions to the study of revivals had been made by Jonathan Edwards. Out of his observations of two important revivals which occurred during his ministry in Northampton, Mass., the first in 1734 and the second in 1740, Edwards published three very important books: A Narrative of Surprising Conversions. Thoughts on the Revival in New England, and A Treatise Concerning Religious Affections. The first of these was read, in the English edition, by John Wesley, thus no doubt greatly influencing the character of the Wesleyan revival. Of the third book a recent writer has said: "Whoever would understand aright the Psychology of Mass Movements in Revivals, which lay hold of communities and pass the boundaries of nations, and even stir continents to their depths, as in the Crusades and at the Reformation, must read Edwards' great work." For more than a century and a half the works of Edwards stood in splendid isolation as the only studies on the psychology of revivals. Finally in 1905, Frederick M. Davenport broke the silence with his book, Primitive Traits in Religious Revivals. Its sound scholarship was immediately recognized and it has long been the standard work on the subject, being copiously quoted by all later writers. The same year saw the publication of a dissertation by a French writer on the psychology of the early American revivals. This work had little circulation and was seemingly soon lost from view. It was no doubt because the interest of the religious world bedame centered in 1904 on the Welsh revival that three volumes on revivals were published within the next three years. Prof. Bois of Montauban made a trip to Wales during which he made careful observations. Upon his return to France he published a study of the Welsh revival,, and a psychological study of revivals in general. Although these works have been somewhat quoted by later writers they have by no means been paid the attention which they merit. In 1907 another French writer, Rogues de Fursac, contributed to the subject, but his work, too, has been in general ignored. Two years later there appeared a book by James Burns under the caption, Revivals: Their Laws and Leaders. The book is a popular presentation of the revivals which had occurred up to and including the Evangelical revival. Only the first chapter actually deals with the psychology of revivals. From 1909 until 1926 not a single book appeared devoted to the subject. In the year 1926, however, there again appeared a book which was the amplification of a dissertation. This study by Dimond deals with the psychology of the Hfesleyan revival. Dimond treats the character and personality of lifesley from the standpoint of a Behaviorist. His discussion of the revival shows also the in- fluence of that school. Previous to this time a number of brief studies of the psychology of revivals had appeared as chapters in books which in the main dealt with other subjects. One of these, however, by Pratt, is without doubt the best and most scholarly study on the subject. Like Davenport's book it has become a classic. (2) THE NEED FOR FURTHER STUDY OF THIS PHENOMENON. From the foregoing resume, the paucity of scholarly work on the psychology of revivals in general is immediately evident. A passing glance will reveal that only two writers have attempted complete and exhaustive scholarly studies of this important phenomenon. Both studies appeared in French, and as no English translations have been made, their influence has not been widely felt. The need for new research on this important subject is evident. Psychology of religion has proved itself an important ally to religion in the gaining of new truth* On every hand there is a demand for, and prognostication of, a new revival of religion. Men are seeking to know what form it will take. Again, a great deal of water has run under psychological bridges since Davenport, Bois, and Rogues de Fursac published their studies. Vast new areas of thought have been opened up in recent years; the Unconscious, of which William James spoke in rather primitive terms has now gained new meaning and content through the work of such men as Freud, Rivers, Pfister, and Myers _; phenomena such as glossolalia, visions, hysteria, etc., can now be examined in new light; the psychology of the crowd is much better understood than in the day of Le Bon's great contribution. C. THE PURPOSE AND PLAN OF THE PRESENT STUDY. With so much new material with which to work, the re-evaluation of this important subject seems exceedingly worth while. The following study will, then, attempt to understand the psychology of religious revivals, not in the light of any one school of psychological thought, but in the light of the newer understanding of truth made possible by the research of many men. The writer has no special thesis to defend, but approaches the subject as one reverently seeking to understand and interpret a great religious phenomenon.
Keywords: Psychology; Religion; Revivals; Edwards; Studies